(untitled) (European Journal of Interdisciplinary Research and Development, 2024)
This article covers veterinary policy in Semirechenskaya oblast in the early 20th century, infectious diseases prevalent among livestock (especially plague), and the activities of veterinary doctors and veterinary paramedics.